2017
DOI: 10.18535/jmscr/v5i9.02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kangaroo Mother Care in Low Birth Weight Babies

Abstract: HR was 146.95 and 139.55, For RR 45.96 and 40.175,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…The effect on respiratory rate is probably due to Kangaroo Mother position which keeps the baby upright inclined at 60°. In our study, there was no difference in oxygen saturation between two groups which are in agreement with the previous studies [13,19,27,28]. However, Almedia et al showed increased SpO2 (93.8% vs. 97.3%) after performing KMC [26].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The effect on respiratory rate is probably due to Kangaroo Mother position which keeps the baby upright inclined at 60°. In our study, there was no difference in oxygen saturation between two groups which are in agreement with the previous studies [13,19,27,28]. However, Almedia et al showed increased SpO2 (93.8% vs. 97.3%) after performing KMC [26].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Almeida et al [26], Miltersteiner et al [27], and Ali et al [13] also did not find any significant change in the heart rate after applying KMC. On the contrary, Phirke et al [19] observed that the heart rate dropped by 3-5 beats per minute during KMC. In contrast to results of our study, Almeida et al [26] [19,28].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…An observational study by Phirke D also showed similar results with stabilization of HR and RR (P <0.0001). 12 Another quasi-experimental study by Azevedo et al in intubated neonates concluded statistically significant decrease in the HR within the normal range with KMC (P<0.001). 11 Thus, the findings of above-mentioned studies were in concordance to the results of present study.…”
Section: Discussionmentioning
confidence: 93%